Elements for Academic Leadership in a Virtual Space - Dustin M. Hebert; Myra Lovett (Ali Khorsandi Taskoh, 2021)
Higher education is facing the need for its leaders to adapt to an ever-increasingly virtual landscape. More than ever before, this became evident during the COVID-19 pandemic, which began in 2020. Previously-utilized leadership strategies proved less than effective tools for managing virtual faculty teams, and new, creative methods of leading people working remotely across wide geographical areas were launched almost overnight. Some worked; some did not. The purpose of this work is to explore the best practices for academic leaders to mentor, motivate, and guide their teams in virtual environments. The themes of creating a culture of trust, team-building and collaboration, and communication emerged in the literature as traits of effective leaders. Here, we apply those traits to personal experiences between March 2020 and May 2021 to propose a model for leadership in a virtual space.